EP.FRI.147 Abdominal Variant Lemierre's Syndrome: A Case Study and literature review. (28th October 2021) - Rawes, Catherine; Badas, Vanessa; Aylward, Kathryn; Whittle, Annika; Brown, Peter; Andreou, Alexandros
Abstract: Background: Lemierre's Syndrome (LS) is a rare condition with a prevalence of around 0.6-2.3 cases per million of population. Typically, LS starts with a Fusobacterium Necophorum oropharyngeal infection which spreads rapidly causing infective thrombophlebitis, classically of the internal jugular. This is a life-threatening condition which left untreated has a mortality of 90%. In less than 10% of LS cases thrombophlebitis occurs outside of the internal jugular vein. These atypical presentations can result in delay in diagnosis thus treatment and hence have an increased risk of mortality. Case Report: Here we present a case report of a patient with Abdominal Variant Lemierre's syndrome. A 47-year-old female with no past medical history was admitted to the emergency department with severe epigastric abdominal pain. The patient was stable, her National Early Warning Score (NEWS) was 2, blood tests on admission showed thrombocytopenia (Hb 121g/dl, Platelets 50x10 9 /l, WCC 17.1x10 12 /l), raised CRP 299mg/l and deranged Liver Function Tests (Total protein 56g/l, Bilirubin 45mg/dl, ALT 94U/L, AlkPhos- 121U/L). A Venous Blood Gas was abnormal with Lactate 2.1mmol/l. A sepsis pathway was initiated. The blood cultures grew Fusobacterium Necophorum . MRI Imaging confirmed the diagnosis of Abdominal Variant Lemierre's Syndrome. Haematology and Microbiology were consulted. The patient was treated with antibiotics and anticoagulation and was discharged 29 days later, she has made a full recovery. Conclusion: This case highlights the importance of sepsis vigilance in Acute General Surgery admissions and emphasises that multidisciplinary teamwork is essential to achieve effective and prompt treatment for patients.